Optimization and Purification of Chitinase Produced by Bacillus subtilis and Its Antifungal Activity against Plant Pathogens - Kavi Karunya, S. (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACT Microorganisms, which secret a complex of mycolytic enzymes are considered to be possible biological control agents of plant diseases. Since Chitinases are digestive enzymes that break down glycosidic bonds in chitin. In this present study, an industrial enzyme chitinase produced by Bacillus subtilis was optimized, purified and its antifungal activity was investigated against plant pathogens. The bacteria Bacillus subtilis was isolated from soil sample and it was identified by staining techniques, plating on selective media and biochemical characteristics. The Bacillus subtilis showed highest chitinolytic activity in Colloidal chitin agars that degrade chitin in 0.6 mm zone of clearance. The production of chitinase by Bacillus subtilis was optimized under different media, substrates, substrate concentrations, pH, temperature and incubation period. The maximum chitinase production was observed in Luria Bertaini Broth amended with 0.3% colloidal chitin at pH 7.0 and temperature 35ËšC after four days of incubation. The enzyme was partially purified by Dialysis method. Protein concentration of 200Âµg/ml was estimated according to Lowryâ€™s method. The Chitinase has antifungal activity against plant pathogens viz, Aspergillus niger, Aspergillus flavus and Penicillium chrysogenum.